A framework to guide the conservation of species hybrids based on ethical and ecological considerations. Issue 4 (14th May 2015) - Jackiw, Raeya N.; Mandil, Ghada; Hager, Heather A.
Abstract Species hybrids have long been undervalued in conservation and are often perceived as a threat to pure species. Recently, the conservation value of hybrids, especially those of natural origin, has gained recognition; however, hybrid conservation remains controversial. We reviewed hybrid management policies, including laws, regulations, and management protocols, from a variety of organizations, primarily in Canada and the United States. We found that many policies are based on limited ethical and ecological considerations and provide little opportunity for hybrid conservation. In most policies, hybrids are either unrepresented or considered a threat to conservation goals. This is problematic because our review of the hybrid conservation literature identified many ethical and ecological considerations relevant to determining the conservation value of a hybrid, all of which are management‐context specific. We also noted a lack of discussion of the ethical considerations regarding hybrid conservation. Based on these findings, we created a policy framework outlining situations in which hybrids could be eligible for conservation in Canada and the United States. The framework comprises a decision tree that helps users determine whether a hybrid should be eligible for conservation based on multiple ecological and ethical considerations. The framework may be applied to any hybrid and is flexible in that it accommodates context‐specific management by allowing different options if a hybrid is a threat to or could benefit conservation goals. The framework can inform policy makers and conservationists in decision‐making processes regarding hybrid conservation by providing a systematic set of decision criteria and guidance on additional criteria to be considered in cases of uncertainty, and it fills a policy gap that limits current hybrid management.